An Analysis of Translation Techniques and Qualities in Terms of Accuracy and Acceptability in Translating Figurative Language in the Movie Songs of Camp Rock 2: The Final Jam - Ika Oktaria Cahyaningrum; Sulistiana Wandasari (English Education Department - Universitas Nasional Karangturi, 2023)
This research focuses on the analysis of translation techniques applied in translating the figurative language in song lyrics in Camp Rock 2: The Final Jam movie and the translation quality in terms of accuracy and acceptability. This research is descriptive qualitative study. The purposes of the research are (1) to find out the figurative language in song lyrics, (2)to describe the techniques used by the translator in translating the figurative language in song lyrics in Camp Rock 2: The Final Jam movie subtitle into Indonesian, and (3) to find out the quality of the translation in terms of accuracy and acceptability. This research was a descriptive qualitative study. The data were the figurative language in song lyrics in Camp Rock 2: The Final Jam movie. The other data were information obtained from the questionnaire distributed to three raters. The total data of the figurative language in song lyric from the movie were 91 data. The analysis on the translation techniques shows that there are three techniques applied in translating the figurative language in song lyrics in Camp Rock 2: The Final Jam movie they are removal of figurative texture, alteration of figurative texture, and identify in figurative texture.